Komunikasi Antarbudaya Dalam Program Acara Sandya Kala Gita (Studi Komunikasi Hindu di Radio Genta Bali) - Budiyasa, I Dewa Gede Putu (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2018)
Intercultural communication aims at forming harmonious life, bringing together two or more people from different cultures to form a new culture. Trust or religion is part of culture. Intercultural communication can basically form a new culture. Mass media plays an important role in people's lives in the process of sending information and reciprocal processes. This paper examines how the intercultural communication process is delivered through Radio media. The process of intercultural communication in the program Sandya Kala Gita is seen as a transactional process that affects the behavior of communicators and communicants intentionally, aware of the behavior to produce messages that are channeled through channels to stimulate or obtain certain attitudes or behaviors. Intercultural communication on the Sandya Kala Gita program shows implications for the strengthening of cognitive communicants, the affective formation of communicators and communicants, and behavioral development for communicators and communicants.